새로운 Aminopyrimidinylmethanone 유도체의 합성 - 유경호; 안혜미 (한국응용과학기술학회, 2009)
In this work, the synthetic approaches for a series of aminopyrimidinylmethanone derivatives la-i, which versatile biological activities such as antibacterial and anticancer activities are expected from a structural point of view, were described. Nicotinic acid was converted to (2-methylsulfonylpyrimidin-4-yl)(pyridin-3-yl)methanone, a key intermediate, which was reacted with nucleophiles to yield the desired aminopyrimidinylmethanone derivatives la-i bearing various substituents.